Africa welcomes new trade initiatives from Japanese investors - Kingsley Ighobor (Africa Renewal, 2017)
African leaders who took part in the Sixth Tokyo International Conference on Africa’s Development (TICAD VI), held last August in Nairobi, Kenya, are eager to test the latest Japanese commitment to investment and development on the continent and how it will improve the quality of life of African citizens.